2010
DOI: 10.1016/j.ijid.2010.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Lower respiratory tract infections among human immunodeficiency virus-exposed, uninfected infants

Abstract: Objectives To evaluate whether maternal HIV disease severity during pregnancy is associated with an increased likelihood of lower respiratory tract infections (LRTIs) in HIV-exposed, uninfected infants. Methods HIV-exposed, uninfected, singleton, term infants enrolled in the NISDI Perinatal Study, with birth weight ≥ 2500 grams were followed from birth until six months of age. LRTI diagnoses, hospitalizations, and associated factors were assessed. Results Of 547 infants, 103 (18.8%) experienced 116 episode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
30
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 27 publications
6
30
0
Order By: Relevance
“…Several HEU studies have noted an association between maternal CD4 and infant hospitalization, [1, 14] mortality [14, 25] and lower respiratory tract infection [26]. We observed an association between maternal HIV viral load and infant pneumonia, but not with CD4, consistent with a South African study [27].…”
Section: Discussionsupporting
confidence: 90%
“…Several HEU studies have noted an association between maternal CD4 and infant hospitalization, [1, 14] mortality [14, 25] and lower respiratory tract infection [26]. We observed an association between maternal HIV viral load and infant pneumonia, but not with CD4, consistent with a South African study [27].…”
Section: Discussionsupporting
confidence: 90%
“…Studies have noted the burden of respiratory tract infections in HEU infants, but without HU control groups, it has not been possible to understand whether HEU infants experience morbidity as expected or morbidity in excess of expected for their context. 4143 In Southern Africa, HEU infants have the same rate of all pneumonia as HU infants but have a greater risk for severe pneumonia and empiric pneumonia treatment failure. 8,13,16,18 Early studies observed a larger relative difference in infant mortality than in morbidity or hospitalization when comparing HEU and HU infants, possibly indicating more severe disease in HEU infants.…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory syncytial virus (RSV) is the most frequent cause of lower respiratory tract infection (LRTI) in young children and by the age of 2 years, 80% of children have encountered the infection . Risk factors pre‐disposing to severe RSV‐related lower respiratory tract infection (LRTI) include prematurity, bronchopulmonary dysplasia, congenital heart disease, and immunodeficiencies . In patients with cystic fibrosis (CF) viral infections have been shown to be associated with increased hospitalization rates and decline in pulmonary function, resulting in short‐term and long‐term morbidity .…”
Section: Introductionmentioning
confidence: 99%